Nonlinear Phenomena of Ultra-Wide-Band Radiation in a Photonic Crystal Fibre - Rim Cherif; Mourad Zghal (International Journal of Optics)
We report the results of a numerical and experimental analysis of femtosecond pulse propagation in a highly nonlinear photonic crystal fibre (PCF). The propagation of ultrashort pulses in PCF is studied taking into account the effects of dispersion, self-phase modulation, stimulated Raman scattering, and self-steepening. The interaction between linear and nonlinear effects is investigated in order to better understand the interplay of these effects leading to the supercontinuum generation. The initial stage of an ultra-wide-band supercontinuum generation under femtosecond pumping is pointed out. Details about the expansion of the blue and red sides of the supercontinuum due to transfer of energy to dispersive waves are revealed and experimentally confirmed. Our experimental results are compared to numerical solution of the nonlinear Schrödinger equation. Good agreement is found.